THE INFLUENCE OF SURFACTANTS ON THE FLAME ATOMIC ABSORPTION DETERMINATION OF HEAVY METALS: UDC 543.422, 661.183.1 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The influence of the different type of surfactants on the analytical signal of flame atomic absorption determination of heavy metals was investigated. The possibility of the decrease of the limit determination of lead, manganese and cadmium at the expense of modificating actions of non-ionic surfactants was shown. On the example of nickel and lead the influence of charge of the surfactant and "magical" action of the critical micelle concentration on the detection sensitivity of atomic absorption determination of heavy metals was shown.
Keywords: -